Seismic vulnerability assessment of precast post-tensioned segmental bridge piers subject to far-fault ground motions. (December 2021) - Ahmadi, Ehsan; Kashani, Mohammad M.
Abstract: Precast post-tensioned segmental (PPS) bridge piers mitigate global and local damages of bridge structures through natural hinges (joints between their segments) and rocking motion of their segments. The application of the PPS piers is currently growing in Accelerated Bridge Construction (ABC) where the segments are manufactured offsite with higher quality, and are assembled onsite in a short time. Structural vulnerability analysis of the PPS piers is very essential in extending their engineering implementation under seismic loading. Thus, this work particularly focuses on seismic vulnerability assessment of the PPS piers. To achieve this goal, a previously developed and experimentally validated robust Finite Element model of the PPS piers in OpenSees programme is used to analyse PPS piers of various aspect ratios. An equivalent reinforced concrete (RC) pier to one of the PPS piers is also analysed. Incremental Dynamic Analysis (IDA) is performed and fragility curves are generated to evaluate seismic performance of the PPS piers and an equivalent RC pier using a suite of 44 far-fault ground motions. The IDA results show that slenderising the PPS pier tends to change the failure criterion from the yielding of the post-tensioning tendon to the strength loss of the pier. For squat and slender piers, the yielding of the tendon governs the failure of the pier while the strength of very slender PPS piers drops due to second-order effects at small drift values prior to the yielding of the post-tensioning tendon. It is also found from fragility curves that squat piers are more prone to seismic collapse compared to slender piers. The equivalent RC pier reaches slight and medium damage states in lower intensity measures compared to the PPS pier.